The Effects of Land Area, Number of Coffee Trees, and Maintenance Costs on Robusta Coffee Production in Duyung Village, Mojokerto Regency - Yose Oentoro; Joko Priyono (Journal of Business Economics and Agribusiness, 2026)
This study aims to examine the role of land area, number of coffee trees, and maintenance costs in determining Robusta coffee production among farmers in Duyung Village, Trawas District, Mojokerto Regency. A quantitative approach was employed using primary data collected through questionnaires distributed to 55 coffee farmers, with the sample size determined using the Slovin formula. The variables analyzed include land area, number of coffee trees, maintenance costs, and Robusta coffee production measured in kilograms. Data were analyzed using multiple linear regression with the assistance of EViews 13 software to evaluate the relationship, magnitude of influence, and statistical significance of each independent variable. The results indicate that land area, number of coffee trees, and maintenance costs simultaneously have a significant effect on Robusta coffee production. Partially, land area (X1) has a positive and significant effect on production, the number of coffee trees (X2) does not have a statistically significant effect, and maintenance costs (X3) have a significant negative effect on production. These findings suggest that land area and efficient management of maintenance costs play a more decisive role in increasing coffee yields, while the number of trees alone is not the main determinant of production. Overall, this study provides empirical evidence on key factors influencing the productivity of Robusta coffee farming and may serve as a reference for developing strategies to improve agricultural productivity in Duyung Village.